IMPLEMENTASI METODE TALAQQI DAN TIKRAR DALAM MENINGKATKAN KUALITAS HAFALAN QURAN SANTRI DI PESANTREN TAHFIDZ MASKANUL HUFFADZ - Ima Maulani Arba’ah; Ahmad Habib; Ahmad Riyadhi Farhan; Zulfitria (Qiro'ah : Jurnal Pendidikan Agama Islam, 2025)
This study aims to examine the implementation of talaqqi and tikrar methods in improving the quality of Qur’anic memorization among students at Maskanul Huffadz Tahfidz Islamic Boarding School. The background of this research is based on the importance of maintaining the quality of Qur’anic memorization, which encompasses not only the quantity of memorized verses but also accuracy of recitation, fluency, and long-term retention. This research employed a qualitative approach with a field research design. Data were collected through observation, in-depth interviews with Qur’an teachers and students, and documentation of learning activities. The findings indicate that the talaqqi method plays a crucial role in ensuring accurate recitation through direct supervision and immediate correction by teachers, while the tikrar method contributes significantly to strengthening memory and maintaining memorization consistency. The integrated application of both methods was found to enhance students’ memorization quality, as reflected in improved fluency, reduced recitation errors, and greater stability of memorization over time. This study concludes that the systematic and continuous implementation of talaqqi and tikrar methods is effective in improving the quality of Qur’anic memorization in a tahfidz boarding school setting.